Assessing the relationship between market orientation and business performance in the hotel industry – the mediating role of service quality - Sampaio, Carlos (2019)
Findings – Research results show that market orientation has a positive direct effect on business performance. Moreover, results indicate that market orientation effects on business performance are mediatedthroughoutthehotels’abilitytoprovideservicequality. Originality/value – Despite the large amount of research on market orientation, research on the hospitalitysectorhasbeen conductedmainlyusing tools developedforthemanufacturingandconsumer goods sectors. On the other hand, little has been done to explore the nature of the mediating effect of service quality on the relationship between market orientation and business performance in the hotel industry. Moreover, despite the contribution of the tourism industry to the Portuguese gross domestic product, researchon thehotelindustryis scarce.